Modelling of business processes of engineering companies at the stages of the life cycle of an investment and construction project - V. I. Paskanny; A. A. Lapidus (Vestnik MGSU)
Introduction. The engineering company ensures the interaction of all participants of the investment and construction project throughout its life cycle and implements a variety of business processes. Due to the fact that an engineering company coordinates the work of design and contracting organizations, suppliers of material and technical resources, the effectiveness of its organizational structure largely determines the efficiency of all participants in an investment and construction project.Materials and methods. The paper defines business processes and organizational structure and shows that for modelling business processes under various organizational structures, the most rational solution is modelling based on queuing networks. As a result, a simulation model of a queuing network was developed for an abstract business process and a simplified organizational structure. The GPSS simulation language was used for software implementation.Results. As a result of the modelling, it is shown that by varying the time indicators of the implementation of business processes and the times of performing various business functions, as well as the quantitative composition of performers in the divisions of an engineering company, it is possible to obtain stable estimates of the effectiveness of its production activities. The main estimates include the average implementation time of the main business processes and the average queue of queries for the implementation of the relevant business processes. Based on the obtained values of these indicators, the management will be able to make more reasonable decisions about the staffing of the engineering company and the transformation of its organizational structure.Conclusions. Modelling is the main mechanism for solving forecasting and optimization problems. Based on the simulation results, it is possible to make an informed decision about the number of employees needed to support a certain group of business processes.